Persepsi Mahasiswa Program Studi Ekonomi Syariah terhadap Implementasi Merdeka Belajar Kampus Merdeka - Siti Hajar Rohaenah; Tuti Kurnia; Wildan Munawar (UNISBA Press, 2022)
Abstract. Independent Learning Campus Independent (MBKM) is a new policy issued by the Minister of Education and Culture of the Republic of Indonesia in 2019 and becomes a new guideline for compiling the current Higher Education curriculum. This research method is a descriptive qualitative research with data collection techniques using a survey through Google Form. This research was conducted at the Department of Islamic Economics, Djuanda University, Bogor in December 2021. The sample was taken from 112 students who filled out a questionnaire from the total active student population of the Islamic Economics study program, amounting to 148 students. The results of the study show the students' perceptions of the Islamic Economics study program on four things, namely 1) The majority of students only know part of the contents of the MBKM policy. 2) Most students are interested in participating in entrepreneurship programs and internships/work practices. 3) The majority of students think that the MBKM program is very useful. 4) Most students have the perception that participating in MBKM activities will incur additional costs outside of University activities. Abstrak. Merdeka Belajar Kampus Merdeka (MBKM) merupakan kebijakan baru yang dikeluarkan menteri Pendidikan dan Kebudayaan Republik Indonesia pada tahun 2019 dan menjadi pedoman baru untuk menyusun kurikulum Perguruan Tinggi saat ini. Metode penelitian ini adalah penelitian kualitatif deskriptif dengan teknik pengambilan data menggunakan survei melalui Google Form. Penelitian ini dilakukan di jurusan Ekonomi Syariah Universitas Djuanda Bogor pada bulan Desember 2021. Sampel diambil dari 112 mahsiswa yang mengisi angket dari total populasi mahasiswa aktif program studi Ekonomi Syariah berjumlah 148 mahasiswa. Hasil penelitian menunjukkan persepsi mahasiswa program studi Ekonomi Syariah terhadap empat hal yaitu 1) Mayoritas mahasiswa hanya mengetahui sebagian isi kebijakan MBKM. 2) Sebagian besar mahasiswa berminat mengikuti program kewirausahaan dan magang/praktik kerja. 3) Mayoritas mahasiswa menganggap bahwa program MBKM sangat bermanfaat. 4) Sebagian besar mahasiswa memiliki persepsi bahwa dengan mengikuti kegiatan MBKM akan mengeluarkan biaya tambahan di luar kegiatan Universitas.